2014
DOI: 10.18512/1980-6477/rbms.v13n3p312-325
|View full text |Cite
|
Sign up to set email alerts
|

Cultivares de Milho em Diferentes Populações de Plantas com Espaçamento Reduzido na Safrinha

Abstract: -The aim of this study was to evaluate the performance of different maize cultivars due to the variation in plant population in reduced row spacing. Two experiments were conducted, the first off-season in 2005 in the municipality of Atalaia, PR (Exp1), and the second off-season in 2007 in the municipality of Alvorada do Sul, PR (EXP2). Both were conducted in crops managed under no-tillage system after crop soybean using 0.45cm row spacing. The randomized complete block design with four replications was adopted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
8
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 16 publications
4
8
0
3
Order By: Relevance
“…The increase was approximately 7%, comparing the smallest population (45 thousand plants ha -1 ) with the largest (90 thousand plants ha -1 ). This result is similar to that found by Marchão, Brasil, Duarte, Guimarães and Gomes (2005) and divergent from that of Foloni et al (2014), who did not observe a relationship between plant height and populations of 39, 52, 79, and 105 thousand plants ha -1 . The height of ear insertion also increased with the increase of the population in both sowing times ( Figure 2C and D), as it had a direct relationship with the height of plants due to elongation of the stem.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The increase was approximately 7%, comparing the smallest population (45 thousand plants ha -1 ) with the largest (90 thousand plants ha -1 ). This result is similar to that found by Marchão, Brasil, Duarte, Guimarães and Gomes (2005) and divergent from that of Foloni et al (2014), who did not observe a relationship between plant height and populations of 39, 52, 79, and 105 thousand plants ha -1 . The height of ear insertion also increased with the increase of the population in both sowing times ( Figure 2C and D), as it had a direct relationship with the height of plants due to elongation of the stem.…”
Section: Resultssupporting
confidence: 91%
“…For example, Kopper et al (2017) found higher corn yield when the cereal was sown in a population of 70 thousand plants ha -1 (above that recommended). While Foloni et al (2014) observed that the best yields were achieved with populations of 81 and 75 thousand plants ha -1 for hybrids AG 9010 and DKB 979, respectively, and both above the recommended population.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Silva Júnior (2010) afirma que o déficit hídrico, de imediato, afeta todos os aspectos relacionados ao desenvolvimento da planta, como redução da taxa fotossintética e área foliar, causados pela diminuição da expansão celular, sendo que nos estádios iniciais ocasiona decréscimo da taxa de crescimento, seguido de menor interceptação da radiação solar. Dentre os fatores que interferem na interceptação da radiação solar tem-se a densidade de plantio, que influencia diretamente na capacidade da cultura cultivada em captar água, luz e nutrientes (FOLONI et al, 2014).…”
Section: Introductionunclassified
“…The overall crop management constraints for soybean -maize off-season succession in Brazil are associated to some aspects related to: low soil cover during the growing season, which can cause grater soil degradation (PACHECO et al, 2013); low use of fertilizers in the maize off-season crop (MAR et al, 2003;SORATTO et al, 2010); anticipation of soybean sowing to middle/late September and early October, when rainfall is highly variable and losses by water deficit normally occurs ; use early soybean cultivars with lower potential yield (FOLONI et al, 2014;NORA et al, 2017); absence of rotation with other crops in the system, favoring the persistence of pests (e.g. Spodoptera frugperda and Helicoverpa zea) and diseases (e.g.…”
Section: Discussionmentioning
confidence: 99%